Effects of changes in short-term human cognition on reported healthcare utilisation. - Richard A Iles; Thomas L Marsh; S M Thumbi; Guy H Palmer (Public Library of Science (PLoS), 2022)
Growing empirical evidence indicates that financial anxiety causes reductions in short-term cognitive capacity. Results from urban communities in Delhi, India show sizable differences in the number of health events recalled between the poor and non-poor respondents over experimentally controlled recall periods. One explanation for this recall difference is 'poor memory'. Such results provide additional reasons for healthy skepticism of the accuracy of self-reported health survey data. The present research identifies which forms of cognitive capacity are related to health event recall and assesses the roles of poverty and illiteracy as mediating variables. Results indicate that underreporting of health events among the poor in rural Kenya is not solely due to 'poor memory'. Data used comes from a repeated cross-sectional study conducted in Samburu county, Kenya over 10-months between 2017-2018. This period coincided with the ending of a protracted and severe drought in East Africa. The results presented in the current study confirm the poor and non-poor distinction, but provide a more detailed cognitive explanation for such results. Reflective throught, as measured by fluid intelligence and heuristic use, is shown to be good predictors of fever recall among relatively poor rura communities in central Kenya.